Factors Affecting Real Estate Project Success: A Systematic Review and Future Agenda - Alka Rani, Dr. Rajwinder Singh (International Journal of Advanced Science and Technology, 2020)
The real estate sector is an emerging sector across the globe. The construction sector assists as a vital pillar in the economic and social development of any country. Infrastructure development is one of the major tools of economic growth of a country. After cultivation industry the construction industry is the second biggest industry of the country. The present scenario’s real estate sector inherently has several different challenges and problems. These challenges have an impact on the success of the projects governed by this sector. Real estate and many housing construction projects have failed to achieve project success due to increase in the challenges and uncertainty. There is a need to review the challenges before this sector as revealed by the previous researchers so that new directions can be provided to the real estate sector for overcoming these challenges and to achieve the long-term growth & development. This study could be of potential value to the real estate sector, particularly in improving their position regarding the ongoing projects. The main objective of this research is to identify the challenges faced by the real estate sector. A systematic approach to review of literature was adopted to achieve the research objective. Various challenges in real estate projects were identified through review of reputed research publications. Therefore the present research is aimed to determine the important factors affecting the effectiveness of managing challenges in housing construction projects. According to a literature review, the most quoted challenges aspects are: safety and Accidents, Manpower Development, Infrastructure, Financial difficulties, Consultant’s related factor, External Factor/ Physical groups, Consultant’s related factor, Raw Materials, Coordination, Operational Factor, Owner groups. This work can provide real estate industry with valuable future directions for developing the next phases challenges identify and control challenges. This study could help the real estate sector, especially in improving their position regarding the ongoing projects.